Midline nasal dermoid cyst with Tessier's 0 cleft - Guruprasad, Yadavalli (Medknow Publications & Media Pvt Ltd, 2014)
This is a rare anomaly of midline nasal dermoid cyst (NDC) along with Tessier's 0 cleft. Midline NDCs present most commonly result from aberrant embryological development, and most commonly give rise to bifid nasal deformity resulting in midline cleft of the nose. Craniofacial clefts are among the most disfiguring of all facial anomalies. They exist in a multitude of patterns and with varying degrees of severity. The bifid nose deformity is generally an indicator of Tessier number 0 cleft. We present a rare combination of midline NDC with a mild Tessier's 0 cleft in a 4-year-old female child who was surgically treated with wide emphasis given on its diagnosis and other treatment modalities.